Diaspore and seedling morphology of Livistona chinensis (Jack.) R. Br. Ex. Mart. (Arecaceae) - Souza, Antonio Maricélio Borges de; Nogueira, Marina Romano; Ferraz, Marcos Vieira; Kobori, Nilce Naomi; Môro, Fabíola Vitti; Pivetta, Kathia Fernandes Lopes (Comunicata Scientiae, 2023)
Knowledge of the anatomical structures of the seed and embryo can contribute to understanding the germination process and interpreting germination and vigor tests. Thus, the objective of this study was to describe morphologically the diaspores (seeds with adhered endocarp) and seedlings of Livistona chinensis. Biometric parameters of the diaspores (width, length, weight of one thousand diaspores, and number of diaspores kg- 1) were collected, and their water content was measured. One hundred diaspores were sown in plastic trays containing vermiculite as a substrate. To describe the morphology of the diaspore and the initial seedling growth, evaluations were performed by monitoring the germination process from the first week, at each stage of development, until the emergence of the first eophyll. Morphological descriptions were based on specific terminology and schematized with the aid of a clear camera attached to a stereomicroscope. Germination is characterized as being of the remote tubular type. The diaspores have an oval shape with an average length of 16.37 mm and an average width of 10.25 mm, and the seeds are albuminous with a rigid endosperm, peripheral lateral cone-shaped embryo, and little differentiation. The first leaf is simple and lanceolate, with parallel venation, composed of broad veins arranged longitudinal.